Neuroanatomical Circuitry between Kidney and Rostral Elements of Brain： a Virally Mediated Transsynaptic Tracing Study in Mice - 周业庭 何志刚 刘涛涛 冯茂辉 张定宇 项红兵 (Journal of Huazhong University of Science and Technology. Medical sciences, 2017)
The identity of higher-order neurons and circuits playing an associative role to control renal function is not well understood. We identified specific neural populations of rostral elements of brain regions that project multisynaptically to the kidneys in 3–6 days after injecting a retrograde tracer pseudorabies virus（PRV）-614 into kidney of 13 adult male C57BL/6J strain mice. PRV-614 infected neurons were detected in a number of mesencephalic（e.g. central amygdala nucleus）, telencephalic regions and motor cortex. These divisions included the preoptic area（POA）, dorsomedial hypothalamus（DMH）, lateral hypothalamus, arcuate nucleus（Arc）, suprachiasmatic nucleus（SCN）, periventricular hypothalamus（Pe H）, and rostral and caudal subdivision of the paraventricular nucleus of the hypothalamus（PVN）. PRV-614/Tyrosine hydroxylase（TH） double-labeled cells were found within DMH, Arc, SCN, Pe H, PVN, the anterodorsal and medial POA. A subset of neurons in PVN that participated in regulating sympathetic outflow to kidney was catecholaminergic or serotonergic. PRV-614 infected neurons within the PVN also contained arginine vasopressin or oxytocin. These data demonstrate the rostral elements of brain innervate the kidney by the neuroanatomical circuitry.